Penguatan Humanisme Pendidikan Agama Islam dalam Mewujudkan Merdeka Belajar di Era Society 5.0 - Novita Nur Hamidah; Suwantoro (Gunung Djati Conference Series, 2022)
In order to fix the education system in Indonesia, the government through the Ministry of Education and Culture made a new breakthrough in the form of a policy of independent learning. The concept of independent learning is more focused on an innovative learning process with great attention to the needs of students. Through this policy, it is hoped that there will be "independence" from every educational activity, especially in learning, including learning Islamic Religious Education. Therefore, to realize all of that, it is felt that there is a need to strengthen the character of humanity (humanism) as a part that should not be eliminated in learning, especially in the era of society 5.0. This research was conducted to examine the strengthening of Islamic religious education humanism in realizing the concept of independent learning in the era of Society 5.0 by using descriptive qualitative research methods with Library Research techniques. The results of this study indicate that the humanism of Islamic Religious Education greatly contributes to realizing the concept of independent learning without neglecting the human aspect of students.